2018
DOI: 10.1007/s11284-018-1632-y
|View full text |Cite
|
Sign up to set email alerts
|

Functional and ecophysiological traits of Halimione portulacoides and Sarcocornia perennis ecotypes in Mediterranean salt marshes under different tidal exposures

Abstract: The present paper aims to discuss the functional and ecophysiological traits of two abundant succulent halophytes in Mediterranean salt marsh systems, considering two ecotypes differing on their tidal exposure. In Halimione portulacoides the higher root/shoot (R/S) biomass ratio verified in low inundation frequency (LF) marshes, as compared with that in high inundation frequency (HF), indicates an optimal partitioning strategy, inducing differential allocation patterns along with varying environmental factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Carotenoids from 30 to 100 µg/g FW (approximate values estimated from graphical representations) were reported by Duarte et al [54] in plants stressed by frequent tidal floods, which decreased with the reduction of the flood frequency. In another study, Duarte et al [55] quantified the leaf carotenoids in about 109-230 µg/g FW, indicatively corresponding to 0.87-1.84 mg/g DW, assuming a moisture of 87.5%, amongst which zeaxanthin was the most abundant.…”
Section: Carotenoidsmentioning
confidence: 56%
“…Carotenoids from 30 to 100 µg/g FW (approximate values estimated from graphical representations) were reported by Duarte et al [54] in plants stressed by frequent tidal floods, which decreased with the reduction of the flood frequency. In another study, Duarte et al [55] quantified the leaf carotenoids in about 109-230 µg/g FW, indicatively corresponding to 0.87-1.84 mg/g DW, assuming a moisture of 87.5%, amongst which zeaxanthin was the most abundant.…”
Section: Carotenoidsmentioning
confidence: 56%
“…However, the increase in glycerol concentration, often in conjunction with arabitol, is a hyperosmotic stress response where glycerol synthesis comes from glucose [ 59 ]. Furthermore, Dias et al [ 35 ] found that a decrease in glucose content and an increase in sugar alcohols suggests that the pool of polyols is maintained at the expense of glucose. The polyols found in plants from Ílhavo have a small concentration of glycerol and myo-inositol.…”
Section: Resultsmentioning
confidence: 99%
“…Some plants may increase the cuticular thickness of leaves, stems, and fruits in response to adverse environmental factors to protect themselves from radiation, prevent water loss, or protect against pathogens [ 62 ]. Plants in aquatic environments have very thin cuticles [ 10 , 35 , 63 ]; however, halophytes are not aquatic but amphibious plants, which may exhibit xeromorphic characteristics, such as cuticular thickening, similar to plants of drought conditions [ 64 ]. This factor prevents excess transpiration and water loss [ 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Buhmann et al [42] reported lower productivity values of 33 g FW m −2 day −1 using very different experimental conditions. These first studies with H. portulacoides (Table 5) already suggest contrasting outcomes, most likely influenced by different culture conditions, genetic variability and the use of different ecotypes [64].…”
Section: Planting Densitymentioning
confidence: 99%